Decline by design: Assessing decline policies as a decarbonisation strategy under the Paris Agreement - Gregory Trencher; Mert Duygan; Adrian Rinscheid; Daniel Rosenbloom; Peter Newell (PLoS ONE, 2025)
Limiting climate change to targets set under the Paris Agreement requires urgent action to reduce the production and use of carbon-intensive technologies, fuels, materials and industrial processes. Accordingly, scholars are increasingly studying ‘decline policies’, which, by design or effect, induce the reduction or discontinuation of carbon-intensive artefacts and activities. However, understanding of the diversity and decarbonisation potential of such policies is hindered by a lack of large-scale, cross-sectoral and cross-national analyses. Here we present a novel dataset of 233 decline policies formulated by the ten highest-emitting Annex I countries to spur decarbonisation. We examine: (1) decline approaches and policies used across sectors; (2) variations in policy design features expected to influence the magnitude of decline and mitigation outcomes; (3) the relationship between decline approaches, policy design features and mitigation impact. We find that decline policies are widely used across the ten countries, including direct approaches (targeting incumbent carbon-intensive elements), and indirect approaches (promoting substitution with cleaner alternatives). Statistical analysis indicates that policy design is a critical determinant of decarbonisation potential. While evidence that direct decline policies might be more effective compared to indirect policies is limited, the ‘intensity’ of decline policies – defined by design features such as strictness, reduction speed and geographic coverage – is significantly associated with higher mitigation impact estimates. Finally, by proposing a typology of archetypical decline policies, our study advances an empirically grounded conceptual framework for understanding decline as a critical strategy for accelerating decarbonisation.